The morphology of ligamentous sacroiliac lesions – challenge to the antero-posterior compression mechanism. Issue 4 (April 2021) - Caterson, A.D.; Olthof, D.C.; Abel, C.; Balogh, Z.J.
Highlights: This computer tomography based observational study describes the pattern of sacroiliac joint opening in pure ligamentous pelvis ring injuries. The inferior part of the sacroiliac joint opens up to a larger extent that the superior part. Ligamentous rotational instability of the pelvis is more likely to be due to a vector of injury from the pelvic floor rather than antero-posterior compression. Abstract: Aim : This paper evaluates computer tomographic morphology of partial ligamentous lesions of the sacroiliac joint. We hypothesised that in antero-posterior compression (APC) injuries the anterior superior portion of the sacroiliac joint (SIJ) should open up the most as suggested by the vector forces outlined in the Young and Burgess classification. Methods: All patients who underwent operative fixation of a ligamentous APC pelvic injury between July 2009 and December 2015 in a single Level-1 trauma centre were included. Patients were case matched (1:1) to controls without pelvic injury. SIJ width was measured by two independent reviewers at the anterior superior and anterior inferior part of the SIJ. Wilcoxon ranged test was applied for analysis. Results: 70 patients (35 cases, 35 controls) were evaluated. Median inferior and superior SI joint widths were 5.27 (IQR 3.68-7.80) and 4.05 (IQR 3.13-5.31) mm in cases versus 2.24 (IQR 1.83-2.50) and 2.44 (IQR 2.14-2.65) mm in controls, respectively. The difference between the inferior and superior SI width in cases was larger than in controls (p-value < 0.01, median of -0.22 mm in the control group versus 1.51 mm in the cases). Conclusion: Our data suggests that the inferior part of the SIJ opens up after injury more, relative to its superior portion. The vector of the force involved in rotationally unstable pelvic injuries is unlikely to be antero-posterior if the force causes the SI joint to widen up inferiorly first. This should be considered in SIJ fixation and challenges the APC mechanism in pure ligamentous rotationally unstable pelvic ring injuries.